Learning during COVID-19: (Too) isolated yet successful - Berens, Florian; Hobert, Sebastian (Frontiers in Education, 2025)
In a world changed by the COVID-19 pandemic, in 2020 universities had to completely rethink and immediately transform their teaching to a fully online setting. As a result, students had to learn from home and organize their learning by themselves. In a natural experiment, data about learning processes indicate that students learned more engaged and achieved higher learning success in this new situation compared to the traditional learning process. However, the students experienced a three-fold isolation: (1) physical isolation, (2) social isolation, and (3) learning isolation, which resulted in a stressful learning experience. In conclusion, these affective challenges indicate that this exceptional learning setting should not be normalized, even though positive outcomes were achieved during COVID-19. Beyond the situation in the pandemic, it can be deduced that students who learn at a distance need additional support to not (only) learn in isolation.